Does interpersonal behavior of psychotherapy trainees differ in private and professional relationships? - Fincke, Janna I.; Möller, Heidi; Taubner, Svenja (Frontiers in Psychology, 2015)
Aim: The present study aimed to evaluate the effect of trainees' interpersonal behaviour on Work Involvement (WI) and compared their social behaviour within professional and private relationships as well as between different psychotherapeutic orientations. Methods: The interpersonal scales of the Intrex short-form questionnaire and the Work Involvement Scale (WIS) were used to evaluate two samples of German psychotherapy trainees in psychoanalytic (PA), psychodynamic (PD) and cognitive behavioural therapy (CBT) training. Trainees from sample 1 (N = 184) were asked to describe their interpersonal behaviour in relation to their patients when filling out the Intrex, whereas trainees from sample 2 (N = 135) were asked to describe the private relationship with a significant other. Results: Interpersonal affiliation in professional relationships significantly predicted the level of Healing Involvement (HI), while Stress Involvement (SI) was predicted by interpersonal affiliation and interdependence in trainees' relationships with their patients. Social behaviour within professional relationships provided higher correlations with WI than private interpersonal behaviour. Significant differences were found between private and professional relation settings in trainees’ interpersonal behaviour with higher levels of affiliation and interdependence with significant others. Differences between therapeutic orientation and social behaviour could only be found when comparing trainees' level of interdependence with the particular relationship setting. Conclusion: Trainees' interpersonal level of affiliation in professional relationships is a predictor for a successful psychotherapeutic development. Vice versa, controlling behaviour in professional settings can be understood as a risk factor against psychotherapeutic growth. Both results strengthen an evidence-based approach for competence development during psychotherapy training.